2014
DOI: 10.1017/s0950268814001241
|View full text |Cite
|
Sign up to set email alerts
|

Diphtheria outbreak in Maranhão, Brazil: microbiological, clinical and epidemiological aspects

Abstract: We describe microbiological, clinical and epidemiological aspects of a diphtheria outbreak that occurred in Maranhão, Brazil. The majority of the 27 confirmed cases occurred in partially (n = 16) or completely (n = 10) immunized children (n = 26). Clinical signs and characteristic symptoms of diphtheria such as cervical lymphadenopathy and pseudomembrane formation were absent in 48% and 7% of the cases, respectively. Complications such as paralysis of lower limbs were observed. Three cases resulted in death, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 26 publications
(54 reference statements)
1
26
1
2
Order By: Relevance
“…The targeted vaccination campaign occurred in May and June, during epidemiological weeks 21-25. During the campaign, the four cases (cases [11][12][13][14] that were identified were not from the schools, or communities near the schools, that had been visited as part of the campaign. There were no further cases reported after the targeted vaccination campaign ended.…”
Section: Targeted Vaccinationmentioning
confidence: 99%
“…The targeted vaccination campaign occurred in May and June, during epidemiological weeks 21-25. During the campaign, the four cases (cases [11][12][13][14] that were identified were not from the schools, or communities near the schools, that had been visited as part of the campaign. There were no further cases reported after the targeted vaccination campaign ended.…”
Section: Targeted Vaccinationmentioning
confidence: 99%
“…Antibiotic resistance in C. diphtheriae remains relatively uncommon, however, a recent report (25) found that C. diphtheriae isolates showed a decreased susceptibility to penicillin and resistance to tetracycline in Rio de Janeiro (25). Multidrug resistant isolates involved in cutaneous and respiratory diphtheria have also been described (26, 27).…”
Section: Discussionmentioning
confidence: 99%
“…A diphtheria epidemic in the former Soviet Union in the 1990s resulted in N 157.000 cases claiming~5000 lives (Dittmann et al, 2000). Yet, this pathogen is not under control, and the have been multiple outbreaks in different countries since 2000 including Colombia (Landazabal et al, 2001), India (Parande et al, 2014;Saikia et al, 2010), Norway (Rasmussen et al, 2011), Nigeria (Besa et al, 2014), Thailand (Wanlapakorn et al, 2014), and more recently in Brazil (Santos et al, 2015), Laos (Nanthavong et al, 2015) and Indonesia (Hughes et al, 2015).…”
Section: Diphtheriae Is Genetically Diversementioning
confidence: 99%